Psikologi Manajemen dalam Pendidikan: Tinjauan Literatur Sistematis tentang Peran Motivasi, Kepemimpinan, dan Pengelolaan Kelas dalam Meningkatkan Efektivitas Pembelajaran dan Kinerja Organisasi - Milda Ajeng Dea R; Adelia Rizky Falela; Ananda Syaiba Suri K; Mualimin Mualimin (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Organizational psychology plays an important role in understanding individual and group behavior within organizations, particularly in educational contexts. Its application can help improve the effectiveness of educational institution management by strengthening key aspects such as work motivation, leadership, communication, and a conducive work environment. By understanding these aspects, educational organizations can develop more effective work systems, enhance the performance of educators, and create a positive and productive organizational culture. However, research on organizational psychology in educational settings remains fragmented and often focuses on specific variables separately. This limits a comprehensive understanding of how these factors interact to influence overall organizational performance. Therefore, a more integrative and comprehensive review is needed to synthesize previous findings. This study aims to review and synthesize existing literature on organizational psychology in educational organizations, with a particular focus on the roles of motivation, leadership, and work environment in improving organizational effectiveness. The findings are expected to provide a more holistic understanding and serve as a basis for developing strategies to enhance the performance of educational organizations in the future.